The concept of "principle" as an element of law - Aleshkova, Irina A. (Linguistics and Culture Review, 2021)
The article is devoted to the characterization of the concept "principle" in jurisprudence. The main approaches associated with the specifics of the expression of the concept "principle" in law (structural and semantic) are identified and analyzed. It is explained that the content of the concept’s "principle" can be replenished with new characteristics, in connection with which there is a need for new forms of their legal verbalization. In the context of law, the understanding of principles is identified with moral values. Among them are individual freedom, conscientiousness, honesty, truthfulness, obedience to the law, love for the Motherland, disinterestedness, tolerance, rejection of violence, theft, slander and envy, kindness and mercy, loyalty to the word, respect for elders, respect for honest work, etc. Attention is drawn to the metaphysical nature of the principles in law, which is expressed, firstly, in the fact that principles in law are a complex multifaceted phenomenon of the synthesis of human consciousness and social practice, in fact, the first reason for the emergence of the norms of constitutional law; secondly, in the fact that they are not formally subject to change in time, they either exist or not, while their content evolves in time and space; thirdly.